Evidence requirements of permanently listed digital health applications (DiGA) and their implementation in the German DiGA directory: an analysis - Melanie Mäder; Patrick Timpel; Tonio Schönfelder; Carsta Militzer-Horstmann; Sandy Scheibe; Ria Heinrich; Dennis Häckl (BMC, 2023)
Abstract Background With its digital health application (DiGA)-system, Germany is considered one of Europe's pioneers in the field of evidence-based digital health. Incorporating DiGA into standard medical care must be based on evidence-based success factors; however, a comprehensive overview of the evidence required of scientific studies for their approval is lacking. Objective The study aims to, (1) identify specific requirements defined by the Federal Institute for Drugs and Medical Devices (German: Bundesinstitut für Arzneimittel- und Medizinprodukte; BfArM) to design adequate studies, proving a positive healthcare effect, and (2) to assess the evidence given for applications permanently listed in the DiGA directory. Methods A multi-step approach was used: (1) identification of the evidence requirements for applications permanently listed in the DiGA directory, (2) identification of the evidence available supporting them. Results All DiGA permanently listed in the DiGA directory (13 applications) are included in the formal analysis. Most DiGA addressed mental health (n = 7), and can be prescribed for one or two indications (n = 10). All permanently listed DiGA have demonstrated their positive healthcare effect through a medical benefit, and most of them provide evidence for one defined primary endpoint. All DiGA manufacturers conducted a randomized controlled trial. Discussion It is striking that- although patient-relevant structural and procedural improvements show high potential for improving care, especially in terms of processes - all DiGA have provided a positive care effect via a medical benefit. Although BfArM accepts study designs with a lower level of evidence for the proof of a positive healthcare effect, all manufacturers conducted a study with a high level of evidence. Conclusion The results of this analysis indicate that permanently listed DiGA meet higher standards than required by the guideline.